Prostaglandin E2 and prostaglandin F2 alpha biosynthesis in human gastric mucosa: effect of chronic alcohol misuse. Issue 3 (September 1996) - Bode, C; Maute, G; Bode, J C
Abstract : BACKGROUND AND AIMS: The results of experimental studies support the hypothesis that decreased prostaglandin production might play a part in the gastric mucosal injury induced by alcohol. In this study, it was investigated whether alcohol misuse impairs the synthesis of prostaglandin E2 (PGE2) and prostaglandin F2 alpha (PGF2 alpha) in gastric mucosa. PATIENTS: Fifty six alcoholic patients and 66 subjects without alcohol misuse were included in the study. METHODS: Mucosal biopsy specimens were obtained from the antrum and body of the stomach. Maximal synthesis rates of PGE2 and PGF2 alpha were determined in the microsomal fraction of the biopsy specimens. RESULTS: The rates of synthesis of both prostaglandins in biopsy specimens from the antrum were not significantly different from those obtained in the body. Synthesis of both prostaglandins was significantly reduced in alcoholic patients who abstained less than five days compared with the non-alcoholic group with normal mucosa (PGE2-40%, PGF2 alpha-42% respectively). In non-alcoholic patients with severe gastritis PGE2 synthesis was increased (+30%, p < 0.05) and PGF2 alpha synthesis was decreased (-42.5%, p < 0.025). In alcoholic patients with severe gastritis PGE2 synthesis was depressed by almost 60% (p < 0.001) compared with the non-alcoholic group with severe gastritis. Neither colonisation of Helicobacter pylori nor smoking had a significant influence on the prostaglandin synthesis. CONCLUSIONS: Chronic alcohol misuse is associated with significantly reduced capacity for prostaglandin synthesis in gastric mucosa and this alcohol induced decrease in prostaglandin synthesis is modulated by the presence and degree of gastritis.